If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8x+3-5x=3-2(x-1)
We move all terms to the left:
8x+3-5x-(3-2(x-1))=0
We add all the numbers together, and all the variables
3x-(3-2(x-1))+3=0
We calculate terms in parentheses: -(3-2(x-1)), so:We get rid of parentheses
3-2(x-1)
determiningTheFunctionDomain -2(x-1)+3
We multiply parentheses
-2x+2+3
We add all the numbers together, and all the variables
-2x+5
Back to the equation:
-(-2x+5)
3x+2x-5+3=0
We add all the numbers together, and all the variables
5x-2=0
We move all terms containing x to the left, all other terms to the right
5x=2
x=2/5
x=2/5
| -38=5(v-8)-7v | | -15+9c=-8+10c | | x+75=-123 | | 15x-2+7×+4=90 | | 2y/3-5=3y/4+1 | | 5x+15-25=12-6x | | 3n+-14=-4 | | 0=-0.01x^2+0.5x+5.9 | | 23-3x=2x+8 | | 17d-15=16d | | 5(x+3)-25=6(2-×) | | 68/28=85/r+12 | | -2+19n=8-1+20n | | 3(x-5)=180 | | -5x/4+5=-5 | | 8x-20=x+5 | | -3x-8+4×=17 | | 10c+10=-10+6c | | 49(x+2)-6(2x+3)=154 | | 1/2x-4/3=-5/7 | | 12.5=2p-3.5 | | 10c+`10=-10+6c | | -6z-2=-13 | | 18=8b+22.8 | | 7g+5=6g | | 4x^2-39x+93.5=0 | | 57p-13p+61p-p=-132 | | 7x-11=-3x+1 | | 8b+10+7b=-3b-8 | | 2(x-9)=-3x-43 | | 4t+25=-3t-38 | | -46p-10=36 |